2004
DOI: 10.1534/genetics.104.029264
|View full text |Cite
|
Sign up to set email alerts
|

GLD-3 and Control of the Mitosis/Meiosis Decision in the Germline of Caenorhabditis elegans

Abstract: Germ cells can divide mitotically to replenish germline tissue or meiotically to produce gametes. In this article, we report that GLD-3, a Caenorhabditis elegans Bicaudal-C homolog, promotes the transition from mitosis to meiosis together with the GLD-2 poly(A) polymerase. GLD-3 binds GLD-2 via a small N-terminal region present in both GLD-3S and GLD-3L isoforms, and GLD-2 and GLD-3 can be co-immunoprecipitated from worm extracts. The FBF repressor binds specifically to elements in the gld-3S 3Ј-UTR, and FBF r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
285
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 162 publications
(297 citation statements)
references
References 41 publications
12
285
0
Order By: Relevance
“…In the gonad, GLP-1 (abnormal Germ Line Proliferation)/Notch signaling is essential to promote germ line divisions in distal mitotic region [19][20][21][22]. GLD (defective in Germ Line Development) family plays a key role in determining meiosis entry and indirectly regulates mitotic proliferation of the germline [23][24][25][26][27]. We found that mir-35 may down-regulate gld-1 to ensure a normal germline proliferation in distal the mir-35 mutant gk262, less intestinal nuclei were observed than the wide type, at 3-fold and L3/L4 stages, respectively (Table 1, P < 0.001, Student t-test).…”
Section: Lacking Mir-35 Causes Decrease Of Intestinal Nuclei Numbersmentioning
confidence: 99%
See 1 more Smart Citation
“…In the gonad, GLP-1 (abnormal Germ Line Proliferation)/Notch signaling is essential to promote germ line divisions in distal mitotic region [19][20][21][22]. GLD (defective in Germ Line Development) family plays a key role in determining meiosis entry and indirectly regulates mitotic proliferation of the germline [23][24][25][26][27]. We found that mir-35 may down-regulate gld-1 to ensure a normal germline proliferation in distal the mir-35 mutant gk262, less intestinal nuclei were observed than the wide type, at 3-fold and L3/L4 stages, respectively (Table 1, P < 0.001, Student t-test).…”
Section: Lacking Mir-35 Causes Decrease Of Intestinal Nuclei Numbersmentioning
confidence: 99%
“…For RNAi experiments in the temperature-sensitive strains, we placed dsRNAs injected worms at 20 °C for 8 h for RNAi to take effect, shifted injected worms to 25 °C and obtained 3-fold embryos (RNAi) developed from laid eggs of RNAi animals. Mutations used in this study were as follows: cdc- 25 The promoter of ges-1 was amplified with the primers 5′ GCG-CATGCTCACCAATACCTTTAGTGAC 3′ and 5′ GGGGATC-CCTGAATTCAAAGATAAGATATGT 3′.…”
Section: Culture Conditions and Strainsmentioning
confidence: 99%
“…Another component of the GLD-1 pathway is NOS-3 (Hansen et al, 2004a). The GLD-2 pathway includes the GLD-2 cytoplasmic poly(A) polymerase (Wang et al, 2002) and GLD-3, an RNA-binding protein (Eckmann et al, 2004). It remains unclear how the regulatory activities of these pathways specifically promote the meiotic cell fate.…”
Section: Introductionmentioning
confidence: 99%
“…These proteins inhibit meiotic entry by preventing translation of the meiosis-promoting genes GLD-1, a translational repressor, and GLD-3, a translational activator, that act along with the poly(A) polymerase GLD-2 and the nanos homolog NOS-3 to coordinate meiotic initiation. [57][58][59] GLD-3 and NOS-3 inhibit FBF-1 and FBF-2 function, maintaining the meiotic state once it has been initiated. 60,61 C. elegans hermaphrodites produce male and female gametes sequentially: the first few rounds of meiosis produce SPERMATOCYTES, and the rest of the GSCs then commit to OOCYTE production for the remainder of the animal's life.…”
Section: Meiotic Initiation and Germ Cell Sex Determinationmentioning
confidence: 99%